Opportunities and Challenges in Implementing the Covid-19 Response Village Programme - Damanik, dhuana Bintang Permata; Tiaisyah, Tiaisyah; ferizaldi, ferizaldi (LPPM Universitas Malikussaleh, 2023)
This study evaluates the implementation of the Covid-19 Response Village Programme in Pulau Tiga Plantation Village, Aceh Tamiang District. The results show that the programme implementation has not run optimally because there are obstacles in several aspects. Firstly, in terms of communication, there is a lack of clarity and consistency of information regarding the prevention and control of Covid-19 delivered by the implementing officers. Secondly, limited human resources have an impact on the ineffective implementation of the prevention programme in this village, and can be seen in several activities that are not carried out optimally. In addition, the lack of facilities and infrastructure, especially the unavailability of a special isolation room, causes people who are positive for Covid-19 to undergo independent isolation in their respective homes. Local community participation is also still low in several prevention activity programmes carried out. To improve programme implementation, corrective measures need to be taken, including the preparation of clearer and more consistent information, increasing human resources involved in the programme, and providing adequate facilities for handling Covid-19. It is expected that with these corrective measures, the implementation of the Covid-19 Response Village Programme can run more effectively in protecting public health and reducing the risk of virus transmission in the village area.